2023
DOI: 10.3390/jcm13010174
|View full text |Cite
|
Sign up to set email alerts
|

Combining Biomarkers for the Diagnosis of Metastatic Melanoma

Tünde Várvölgyi,
Eszter Anna Janka,
István Szász
et al.

Abstract: The early detection of melanoma relapse can improve patient survival; thus, there is a great need for easily accessible biomarkers that facilitate the diagnosis of metastatic disease. We investigated the diagnostic effect of blood biomarkers such as lactate dehydrogenase (LDH), S100B, and osteopontin in the detection of metastases. Clinical data and peripheral blood samples of 206 melanoma patients were collected (no metastasis, N = 120; metastasis, N = 86). The discriminative power of blood biomarkers, patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…In the study of Várvölgyi et al, it was revealed that plasma osteopontin levels displayed a significant association with the probability of metastatic melanoma, which was similar to serum S100B levels. Moreover, this publication underlines that combining different biomarkers shows great clinical potential [ 7 ]. The role of aquaporin transmembrane proteins is intensively investigated in cancer biology [ 8 , 9 ].…”
mentioning
confidence: 99%
“…In the study of Várvölgyi et al, it was revealed that plasma osteopontin levels displayed a significant association with the probability of metastatic melanoma, which was similar to serum S100B levels. Moreover, this publication underlines that combining different biomarkers shows great clinical potential [ 7 ]. The role of aquaporin transmembrane proteins is intensively investigated in cancer biology [ 8 , 9 ].…”
mentioning
confidence: 99%